712. Risk of Infective Endocarditis after Transcatheter Aortic Valve Replacement in Patients with Bloodstream Infection: A Population-Based Study. (31st December 2020) - Talha, Khawaja M; McHugh, Jack; DeSimone, Daniel; Baddour, Larry M; Baddour, Larry M; Sohail, M Rizwan; Lahr, Brian; Eleid, Mackram; Sauver, Jennifer St
Abstract: Background: Transcatheter aortic valve replacement (TAVR) was initially approved as an alternative to surgery for patients at high surgical risk. However, it is now being considered for patients with intermediate and low surgical risk. This will result in the expansion of patient pool for TAVR; hence it is of interest to ascertain risk of blood stream infection (BSI) and infective endocarditis (IE) following TAVR. We aim to study the incidence, epidemiology and risk factors associated with IE in patients who underwent TAVR and subsequently developed a BSI. Methods: A population-based study was conducted in 7 counties in southeastern Minnesota using the expanded Rochester Epidemiology Project (E-REP) for all adult (≥18 years) patients who underwent TAVR from January 1 st, 2010 to December 31 st, 2018. Transcatheter procedures that included replacement of either the aortic or mitral valve were included. Medical records were screened for development of BSI from time of TAVR until May 15 th, 2020. Patients were classified as having BSI only, BSI with IE at outset, or BSI with subsequent development of new IE. 'Early' IE was defined as that occurring < 12 months following TAVR, with subsequent cases defined as 'late' IE. Results: A total of 247 patients underwent TAVR during the study period. There were 24 patients with of BSI and 10 (42%) developed IE with an annual incidence of 5 per 1000 persons-years. Median age for patients who developed IE was 85.4 years. Male gender was affected predominantly (70%). Six developed IE at outset of BSI, while four developed IE subsequent to IE. The median time to development of IE was 791 days following TAVR. There was an equal number of early and late IE cases (n=5). The most common pathogen causing IE was viridians group streptococci (n=4) followed by enterococci and coagulase-negative staphylococci with 2 patients each. Mean Charlson comorbidity index was 6.6. Two patients with IE died before resolution of infection (20%). Conclusion: The incidence of BSI and subsequent IE in patients with TAVR was low in our population. Due to the small number of BSI and IE cases, statistical analysis was not feasible. An analysis of all cases seen at Mayo Clinic is planned since the number of cases would be much higher to investigate potential risk factors associated with BSI and IE. Disclosures: Larry M. Baddour, MD, Boston Scientific (Consultant) M. Rizwan Sohail, MD, Aziyo Biologics (Consultant)Medtronic Inc (Consultant, Research Grant or Support)